Development of cyclosporine A microemulsion for parenteral delivery. (May 2015) - Yuan, Yue; Che, Xin; Zhao, Mingyi; Wang, Yan; Liu, Yajun; Schwendeman, Anna; Li, Sanming
Abstract The goal of this study was to develop a parenteral microemulsion formulation of cyclosporine A (CyA). The CyA solubility in caprylic capric triglyceride (GTCC), ethyl oleate and soybean oil were determined. The pseudo-ternary diagrams of oil (GTCC), surfactant (Solutol® HS-15), cosurfactants (ethanol/polyethylene glycol 400 [PEG 400] mixture) and water were constructed to identify boundaries for microemulsion existence. The CyA was added at 3, 6 and 9% w/w to the optimal microemulsion composition. Microemulsion particle size, solution viscosity and conductivity were examined. The microemulsion stability and haemolytic potential were examined after dilution in 5% dextrose solution for injection to 1 mg/mL CyA. Microemulsion stability was examined after a three-month storage at 4 and 25 °C. The GTCC was selected as an oil phase for CyA microemulsion based on solubility results. The optimum CyA microemulsion formulation consisted of 2.5% CyA, 9% GTCC, 24% Solutol® HS 15, 8% PEG 400, 4% ethanol and 52.5% water based on weight percent. The average particle sizes of the optimized blank and drug-loaded microemulsions were 68.7 nm and 71.6 nm, respectively and remained unchanged upon 25-fold dextrose dilution. The results of microemulsion physical and CyA chemical were confirmed by a three-month stability study at 4 and 25 °C. In vitro haemolysis studies indicated that CyA microemulsions were well tolerated by erythrocytes. The novel microemulsion formulation of CyA was developed that is suitable for parenteral administration. This new formulation could potentially have less vehicle-associated side effects that current commercial formulation of CyA based on Cremophor® EL and ethanol solution.